Pengaruh Perkembangan Karir terhadap Komitmen Karyawan Kantor Wilayah II PT. Bank Syariah Mandiri Kota Jakarta - Albertus Saptoprijono (UniSadhuGuna Business School, 2020)
This research aims to analyze the effect of career development towards commitment staff commitment. Data used in research from qustioner dan direct observation in field. Data analysis used of Multiple Regression. Research’s result show that commitment is negatively affected bycareer development based on eduaction dan training, while performance and performance appraisal, mutation and promotion have a positive affection. That means staff’s commitment determined by performance and performance apprasial, mutation and promotion job position at Regional Office II PT. Bank Syariah Mandiri.